2015
DOI: 10.1007/s10997-014-9305-x
|View full text |Cite
|
Sign up to set email alerts
|

Revamping research on unrelated diversification strategy: perspectives, opportunities and challenges for future inquiry

Abstract: With the aim of achieving an advanced understanding of current research on unrelated diversification and providing fruitful groundwork to foster active interchange between disciplinary traditions, this paper detects articles from two relevant research streams; i.e., strategic management and financial economics. We first provide a brief overview of management thinking on unrelated diversification strategy. Then, we present a conceptual map that offers a comprehensive appreciation of unrelated diversification st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 258 publications
(259 reference statements)
0
15
0
Order By: Relevance
“…Diversification into different markets should be conducted within a firm's management capability (Holder & Zhao, 2014). UPD draws attention to generating firm performance in the short run because of not only the new growth opportunities in terms of market‐to‐book ratio (Holder & Zhao, 2014), but also the advantages of risk reduction, and distribution of financial resources and investment funds (Picone & Dagnino, 2016). However, due to the difficulties to maintain efficient management and focus leadership only on the new areas, firms that adopt a UPD strategy encounter high costs such as governance and coordination costs in the intermediate term (Chen et al, 2012).…”
Section: Theoretical Background and Modelingmentioning
confidence: 99%
“…Diversification into different markets should be conducted within a firm's management capability (Holder & Zhao, 2014). UPD draws attention to generating firm performance in the short run because of not only the new growth opportunities in terms of market‐to‐book ratio (Holder & Zhao, 2014), but also the advantages of risk reduction, and distribution of financial resources and investment funds (Picone & Dagnino, 2016). However, due to the difficulties to maintain efficient management and focus leadership only on the new areas, firms that adopt a UPD strategy encounter high costs such as governance and coordination costs in the intermediate term (Chen et al, 2012).…”
Section: Theoretical Background and Modelingmentioning
confidence: 99%
“…At the same time, however, the study also emphasizes the importance of unrelated diversification to be applied in the workplace. It suggests that unrelated diversification can lead to knowledge accumulation that is more innovative than related diversification [59]. Exploring unrelated diversification helped in the case of Maeil as the firm avoided core rigidity that could have simply trapped Maeil in the dairy industry.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Extant literature has investigated empire building from different angles. For example, scholars have identified and demonstrated that empire building is one of the managerial drivers for corporate strategic decisionmaking in unrelated diversification (Picone and Dagnino, 2016) and overinvestment (Wojahn, 2012). A number of studies have shed light on how firm level antecedents of cash holding (Iskandar-Datta and Jia, 2014) and SG&A costs stimulate empire building within the context of managerial discretion and investor protection (Namitha and Shijin, 2016).…”
Section: A Theoretical Framework Of Empire Buildingmentioning
confidence: 99%
“…Literature defines empire building as the economically unjustifiable corporate growth of a firm (Iskandar-Datta and Jia, 2014;Jensen, 1986;Schumpeter, 1934;Stulz, 1990). It is a suboptimal managerial strategy when viewed under a shareholders' perspective as it underscores the violation of fiduciary obligations of top executives (Iskandar-Datta and Jia, 2014;Zhang, 2014), and deviates from operational and economic efficiency (Chen and Young, 2010;Picone and Dagnino, 2016;Wojahn, 2012).…”
Section: Introductionmentioning
confidence: 99%